2019
DOI: 10.17219/acem/92012
|View full text |Cite
|
Sign up to set email alerts
|

VEGF serum concentration and irreversible bronchoconstriction in adult asthmatics

Abstract: Background. Vascular endothelial growth factor (VEGF) is an angiogenic, heparin-binding glycoprotein playing an important role in the pathogenesis of many diseases and disorders, including asthma. It has been reported that increased VEGF serum concentration is a biomarker of neovascularization, which could suggest that higher VEGF expression may be relevant to asthmatics with airway remodeling and irreversible bronchoconstriction. Objectives. The aim of this study was to assess the possible association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…VEGF induced by allergic reaction, facilitates vascular remodeling as well as angiogenesis that is linked with airway remodeling [39]. The levels of VEGF have been shown to be increased in chronic lung diseases [40]. In accordance with previous findings [41], in the present study, an increase in levels of VEGF in B(a)P-induced lung injury rat models was noted, whereas VEGF levels were significantly decreased in the B(a)P + ADE-treated group.…”
Section: Discussionsupporting
confidence: 91%
“…VEGF induced by allergic reaction, facilitates vascular remodeling as well as angiogenesis that is linked with airway remodeling [39]. The levels of VEGF have been shown to be increased in chronic lung diseases [40]. In accordance with previous findings [41], in the present study, an increase in levels of VEGF in B(a)P-induced lung injury rat models was noted, whereas VEGF levels were significantly decreased in the B(a)P + ADE-treated group.…”
Section: Discussionsupporting
confidence: 91%
“…What is more, Fortunati et al [ 22 ] compared the presence of markers on blood cells and tissue cells obtained from sputum and BAL and revealed that cells homing to the tissue under homeostatic conditions exhibit the same phenotype. In our previous study we have shown that an increased VEGF serum concentration is characteristic for patients with asthma, especially those with irreversible bronchoconstriction [ 23 ]. In other papers [ 24 , 25 ], matters of basophils VEGF-activation and the potential contribution of VEGF gene polymorphism to the spontaneous increase of eosinophils activity (priming) in patients with asthma were suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF) promotes vascular endothelial cell proliferation, inducing angiogenesis and increasing microvascular permeability [ 8 ]. The VEGF level in the bronchoalveolar lavage fluid of asthma patients is higher than that of healthy controls, whereas VEGF overexpression in induced sputum and plasma correlates with disease severity [ 9 ]. VEGF induces vascular endothelial growth, participates in chronic airway inflammation and mucosal neovascularization, and negatively correlates with tracheal lumen diameter [ 10 ].…”
Section: Introductionmentioning
confidence: 99%